Forgiving Others towards Self-Happiness: A Meta-Analysis Review - Handayani, Arifah; Kasturi, Taufik; Purwandari, Eny (Journal of Educational, Health and Community Psychology, 2024)
This article presents a meta-analytic study examining the relationship between forgiving others and personal happiness. Data were collected from fifteen sources across thirteen articles, involving a total of 6,651 participants (57% female; 43% male). The results, using a random effects model, indicate a significant positive relationship between forgiveness and happiness (z = 5.793; p < 0.001; 95% CI (0.179; 0.360)). The correlation is moderate, with the confidence interval ranging from 0.179 to 0.361. This meta-analysis supports previous studies that suggest a positive correlation between forgiving others and increased happiness. Specifically, individuals who are willing to forgive tend to experience higher levels of happiness compared to those who do not forgive. Age and country of origin showed no significant differences. The implications of this study suggest that age and country of origin are not relevant factors for justifying a lack of forgiveness